Fundamentals of Teaching Karakalpak Language Competence - Seytkasimov, D. B. (International Journal on Human-Computing Studies, 2023)
There are many connections in science, and they can be given for various reasons - by scientific discipline, by the object of application, organizational and others. When forming linguodidactic competencies, it is necessary to determine the relationship of communication that has developed during the training of teachers of the Karakalpak language on the basis of competence-based communication with other methodological communication.